Extreme precipitation events in bauru-sp: Possibility of occurrences of natural disasters? - Machado, Jeferson Prietsch [UNESP]; Machado, Cristiane Ferrari Canez [UNESP]; Schiewaldt, Caio Brandão [UNESP] (Universidade Federal do Rio de Janeiro, 2019)
The present work seeks to approach the natural disasters and extreme events that affect the southeast of Brazil, specifically the municipality of Bauru, in the state of São Paulo. Firstly, the text brings some theoretical aspects and conceptualizations on these themes. In addition, this work also seeks to bring some elements of the Social Assistance Policy, in view of the fact that this policy helps in the process involving natural disasters. Subsequently, information on the extreme events occurring in the municipality will be presented from the precipitation data of the automatic station of the IPMet between the years of 2001 and 2017. The results indicate the occurrence of extreme event when the cumulative precipitation in 24 hours is equal to or greater than 71.5 mm, and this occurred 16 times during this period. Of all these extreme events occurred, only 7 were considered as natural disasters, based on classifying the IPMet database and COBRADE. However, to classify an event as a natural disaster, we must consider other factors such as the severity and impact of natural disasters, especially the consequences for the population, which is always the most affected.
Eventos extremos de precipitação no município de Bauru-SP: Possibilidade de ocorrências de desastres naturais?
Keywords: Extreme events; Natural disasters; Precipitation; Social Assistance Policy